(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose– This paper tries to elaborate the need of Supply Chain Management in the area of Healthcare services. Health care organisations have recognized the importance of supply chain management practices and are adopting the techniques, methods for improvement.